2017
DOI: 10.1016/j.yjmcc.2017.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Class I HDACs control a JIP1-dependent pathway for kinesin-microtubule binding in cardiomyocytes

Abstract: Class I histone deacetylase (HDAC) inhibitors block hypertrophy and fibrosis of the heart by suppressing pathological signaling and gene expression programs in cardiac myocytes and fibroblasts. The impact of HDAC inhibition in unstressed cardiac cells remains poorly understood. Here, we demonstrate that treatment of cultured cardiomyocytes with small molecule HDAC inhibitors leads to dramatic induction of c-Jun amino-terminal kinase (JNK)-interacting protein-1 (JIP1) mRNA and protein expression. In contrast to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 43 publications
(49 reference statements)
0
6
0
Order By: Relevance
“…As discussed above, HDAC inhibitors are efficacious in pre-clinical animal models of HF [6,7,8,11,14,23,43,49]. However, molecular underpinnings for HDAC inhibitors in the heart have largely focused on their role in the regulation of histone (de)acetylation and gene expression [47,93]. Recent reports, however, have shown that HDAC inhibitors can target cytosolic and sarcomere proteins to improve cardiac function via improvements in muscle contractility [7], relaxation [14], autophagy [11], and proteotoxicity [8].…”
Section: Hdac Inhibition Protein Phosphorylation and Heart Failurementioning
confidence: 99%
“…As discussed above, HDAC inhibitors are efficacious in pre-clinical animal models of HF [6,7,8,11,14,23,43,49]. However, molecular underpinnings for HDAC inhibitors in the heart have largely focused on their role in the regulation of histone (de)acetylation and gene expression [47,93]. Recent reports, however, have shown that HDAC inhibitors can target cytosolic and sarcomere proteins to improve cardiac function via improvements in muscle contractility [7], relaxation [14], autophagy [11], and proteotoxicity [8].…”
Section: Hdac Inhibition Protein Phosphorylation and Heart Failurementioning
confidence: 99%
“…Whereas, inhibition of JNK and ERK was sufficient to attenuate gene expression of selected genes; our data do not infer that anti-inflammatory actions were solely the result of ERK and JNK signaling. With respect to the literature, in which HDACs have been shown to regulate NF-κB (S. Chen et al, 2018), JAK/STAT (S. Chen et al, 2018;Yang & Seto, 2008), MAPKs (Blakeslee et al, 2017;Ferguson et al, 2013), and PI3K/AKT (Yang & Seto, 2008) among others; we would postulate that anti-inflammatory actions mediated by HDAC inhibitors are a result of MAPK inhibition in combination with changes in other signaling cascades. Assessment of these intracellular pathways in bovine MAC-Ts would be interesting to explore.…”
Section: Discussionmentioning
confidence: 99%
“…KIF5A was reported to be involved in the transport of lysosomes, synaptic vesicle precursors, other diverse vesicles, and mitochondria (Morfini et al 2016). This kinesin also regulates the intracellular transport of cargo, such as autophagosomes, in cardiomyocytes (Blakeslee et al 2017). To note, the deficiency in KIF5A induces epilepsy in both humans (Dixit et al 2016) and mice (Nakajima et al 2012) and is also associated with myoclonic seizures in humans (Rydzanicz et al 2017).…”
Section: Autophagy In Tmt-induced Neurotoxicitymentioning
confidence: 99%